Impact of skilled nursing facility (SNF) 3‐day hospitalization requirement waiver during the COVID‐19 pandemic on emergency department and inpatient SNF discharges in California - Theodore C. Chan; Jesse J. Brennan; Edward M. Castillo (Journal of the American College of Emergency Physicians Open)
Abstract Objective We sought to study the impact of the Centers for Medicare & Medicaid services (CMS) waiver of the 3‐day hospitalization requirement for skilled nursing facility (SNF) care implemented as part of the Federal COVID‐19 response on emergency department (ED) and inpatient hospital SNF discharges. Methods We conducted a multicenter retrospective cohort study of hospital ED and inpatient visits in California during 18 months before (prewaiver, September 2018–February 2020) and 18 months after (waiver, March 2020–August 2021) waiver implementation. Data were collected from all adult ED and admitted patients utilizing California Department of Health Care Access and Information datasets from all acute care hospitals licensed in the state. Prewaiver and waiver periods were compared for SNF discharge/disposition rates stratified by patient demographic and hospital data with differences in the proportion and 95% confidence interval [CI] reported (SPSS). Results SNF discharges decreased from the prewaiver to waiver periods from the ED (−7.4% [CI −8.1%, −6.6%]), along with larger declines occurring from the inpatient hospital setting (−18.1% [CI −18.4%, −17.9%]). For Medicare beneficiaries, there was a smaller decrease in ED SNF rates (−3.8% [CI −4.7%, −2.9%]), and there was no significant change for SNF discharge rates for inpatient admissions with a length of stay (LOS) <3 days (+1.0% [CI 0.0%, 2.1%]). Conclusion In California, the CMS waiver did not result in an increase, but an actual decrease rate of SNF discharges from the ED and inpatient setting, though with smaller declines for the ED, Medicare patients, and those with a LOS <3 days.